Sistem Deteksi Gejala Hipoksia Berdasarkan Saturasi Oksigen dan Detak Jantung Menggunakan Metode Fuzzy Berbasis Arduino - Dian Bagus Setyo Budi; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The rapid development of intelligent systems is highly developed, one of them in the health or medical fields. In the medical field, a tool is needed to observe the patient's condition in a noninvasive way without injuring the patient. If it is ignored continuously then hypoxia can interfere with the function of the brain, liver, and other organs quickly. So that in this study a hypoxic early symptom detection tool that uses a noninvasive method using the Max30100 sensor that is clipped to the fingertip can be made to determine the results of the initial symptoms of hypoxia. To detect the initial symptoms of hypoxia in this tool, the Sugeno fuzzy method is used so that output is obtained according to the existing rules. Sugeno fuzzy method will process data taken from the Max30100 sensor. There are 3 hardware devices that are on this device, the Arduino microcontroller as the controller, the Max30100 sensor to get the input and Bluetooth for sending data to the smarthphone. Software uses the Arduino IDE to program detection devices and APP inventors to program android applications so they can display data. In this study, the test results were obtained and the results of the test obtained a tool error of 2.96% for oxygen duration and 2.86% for heart rate obtained. From the fuzzy method on 12 data experiments, 100% accuracy was obtained and the Sugeno fuzzy method was able to process the input data properly.